Mechanochemical interactions in cancer cells: The role of substrate stiffness in cell behavior and drug response - Sayed Reza Ramezani; Afsaneh Mojra; Mohammad Tafazzoli-Shadpour (PLoS ONE, 2026)
Cancer cells adhere to the extracellular matrix, where they sense and respond to variations in substrate stiffness, influencing their proliferation and invasive potential. Numerous studies have examined the biological activities of cells in relation to mechanical forces; however, research addressing the combined effects of mechanical and chemical interactions on cancer cell behavior across different metastatic stages remains limited. Moreover, the influence of chemotherapeutic drugs in the context of specific cellular characteristics remains underexplored. Therefore, in this study, synthetic polyacrylamide gels with varying elastic moduli were utilized to effectively mimic the diversity of host tissue environments for prostate cancer cells. Additionally, cellular behavior of prostate cancer cells with differing metastatic potential—low (LNCaP), medium (DU145), and high (PC3)—was evaluated in response to anticancer drugs. Ultimately, effects of drug treatment were comprehensively examined using Docetaxel, Bicalutamide, and Abiraterone Acetate, which target distinct cellular components and activate diverse signaling pathways. The assessments were based on the analysis of actin filament content and organization, size of nucleus, and cellular elastic modulus. The results revealed that a soft substrate improves the medication efficacy, resulting in an enhanced cell death rate of 40–60% compared to 20–30% on a stiff substrate. Cells cultured on soft substrates exhibited lower phalloidin content (8–16%) compared to those on stiff substrates (18–32%). Additionally, drug treatments influenced cell mechanics, with Docetaxel reducing the elastic modulus, while Bicalutamide induced an increase. Based on these findings, a treatment strategy aimed at enhancing therapeutic efficacy can be proposed.